Quercetin as a possible complementary agent for early-stage COVID-19: Concluding results of a randomized clinical trial - Francesco Di Pierro; Francesco Di Pierro; Amjad Khan; Somia Iqtadar; Sami Ullah Mumtaz; Muhammad Nabeel Akbar Chaudhry; Alexander Bertuccioli; Giuseppe Derosa; Giuseppe Derosa; Pamela Maffioli; Stefano Togni; Antonella Riva; et al. (Frontiers in Pharmacology, 2023)
Background: Quercetin, a natural polyphenol with demonstrated broad-spectrum antiviral, anti-inflammatory, and antioxidant properties, has been proposed as an adjuvant for early-stage coronavirus disease 2019 (COVID-19) infection.Objective: To explore the possible therapeutic effect of quercetin in outpatients with early-stage mild to moderate symptoms of COVID-19.Methods: This was an open-label randomized controlled clinical trial conducted at the department of medicine, King Edward Medical University, Lahore, PK. Patients were randomized to receive either standard of care (SC) plus an oral quercetin supplement (500 mg Quercetin Phytosome®, 1st week, TDS: 2nd week, BDS) (n = 50, quercetin group) or SC alone (n = 50, control group).Results: After one week of treatment, patients in the quercetin group showed a speedy recovery from COVID-19 as compared to the control group, i.e., 34 patients (vs. 12 in the control group) tested negative for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) (p = 0.0004), and 26 patients (vs. 12 in the control group) had their COVID-19-associated acute symptoms resolved (p = 0.0051). Patients in the quercetin group also showed a significant fall in the serum lactate dehydrogenase (LDH) mean values i.e., from 406.56 ± 183.92 to 257.74 ± 110.73 U/L, p = 0.0001. Quercetin was well-tolerated by all the 50 patients, and no side effects were reported.Conclusion: Our results, suggest the possible therapeutic role of quercetin in early-stage COVID-19, including speedy clearance of SARS-CoV-2, early resolution of the acute symptoms and modulation of the host’s hyperinflammatory response.Clinical Trial Registration:clinicaltrials.gov, identifier NCT04861298